Making education work : technical studies, position papers and reports of educators and sectoral representatives. (Quezon City, Philippines : Congressional Oversight Committee on Education, 1993)
The four books comprising the entire report of the Congressional Commission on Education (EDCOM) are the product of a twelve-month intensive study of the state of education and training in the Philippines... Books One and Two look at the education scene in depth: the first, in terms of areas of concern that seem to be true of all types and levels of eduction; the second, in terms of the levels of education... Book Three capsulizes views, and suggestions from multi-sectoral groups who are the givers and receivers of education services... Book Four comprises selected technical papers by academics, professionals and field managers who participated actively in EDCOM consultations as well as thoughtful discourses from EDCOM resource persons and consultants.
I. Philosophy of education -- II. issues, concerns and problems of education -- III. Decentralization and restructuring of the educational system -- IV. Governance and financing -- V. Curriculum and degree programs -- VI. Language and the language of instruction -- VII. Higher, professional and graduate education -- VIII. Research -- IX. Special education -- X. Testing, evaluation and guidance counseling -- XI. Teacher development -- XII. Teacher Organization and welfare -- XIII. Libraries -- XIV. Linkages -- XV. Health -- XVI. Education of cultural communities.
Keywords: EDUCATION